ASSESSING THE EFFECTIVENESS OF CIRCULAR ECONOMY INDICATORS IN MEASURING SUSTAINABILITY PERFORMANCE IN THE TEXTILE INDUSTRY - Dustkobilov Ulugbek (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
The textile industry, a major contributor to global environmental degradation, generates 92 million tons of waste annually, with only 1% recycled, necessitating robust circular economy (CE) practices to enhance sustainability. This article evaluates the effectiveness of CE indicators—such as the Material Circularity Indicator (MCI), recycling rates, water usage, and carbon footprints—in measuring sustainability performance in the textile sector. Through a mixed-methods approach, including literature reviews, case studies from the EU, Bangladesh, and India, stakeholder interviews, and quantitative data analysis, the study identifies strengths, such as accurate material flow tracking, and limitations, including data inconsistencies, neglect of social impacts like labor conditions, and regional disparities. Findings reveal that while EU policies drive precise metrics, developing nations face infrastructure and data challenges. The article proposes refined indicators, including a Localized Circularity Index, Social Impact Metric, and Supply Chain Transparency Score, to address these gaps. By offering actionable recommendations for policymakers and industry leaders, this study contributes to advancing CE implementation, critical for achieving 2030 sustainability goals in a high-impact industry.